T Cells in Fibrosis and Fibrotic Diseases - Zhang, Mengjuan; Zhang, Song (Frontiers in Immunology, 2020)
Fibrosis is the extensive deposition of fibrous connective tissue, characterized by the accumulation of collagen and other extracellular matrix (ECM) components. Fibrosis is essential for wound healing and tissue repair in response to a variety of triggers, which include infection, inflammation, autoimmune disorder, degenerative disease, tumor, and injury. Fibrotic remodeling in various diseases, such as liver cirrhosis, pulmonary fibrosis, renal interstitial fibrosis, myocardial infarction, systemic sclerosis (SSc), and graft-versus-host disease (GVHD), can impair organ function, causing high morbidity and mortality. Both innate and adaptive immunity are involved in fibrogenesis. Although the roles of macrophages in fibrogenesis have been studied for many years, the underlying mechanisms concerning the manner in which T cells regulate fibrosis are not completely understood. The T cell receptor (TCR) engages the antigen and shapes the repertoire of antigen-specific T cells. Based on the divergent expression of surface molecules and cell functions, T cells are subdivided into natural killer T (NKT) cells, γδ T cells, CD8+ cytotoxic T lymphocytes (CTL), regulatory T (Treg) cells, T follicular regulatory (Tfr) cells, and T helper cells, including Th1, Th2, Th9, Th17, Th22, and T follicular helper (Tfh) cells. In this review, we summarize the pro-fibrotic or anti-fibrotic roles and distinct mechanisms of different T cell subsets. On reviewing the literature, we conclude that the T cell regulations are commonly disease-specific and tissue-specific. Finally, we provide perspectives on microbiota, viral infection, and metabolism, and discuss the current advancements of technologies for identifying novel targets and developing immunotherapies for intervention in fibrosis and fibrotic diseases.